1999
DOI: 10.1001/archpedi.153.8.808
|View full text |Cite
|
Sign up to set email alerts
|

Infant Health Care Use and Maternal Depression

Abstract: To determine whether women who frequently bring their neonates for problem-oriented primary care visits or emergency department visits are at elevated risk of having depressive symptoms. Design: Analysis of 2 prospective cohort studies of mothers and their infants: (1) a telephone interview study of mothers and infants after birth at an urban teaching hospital (the hospital cohort) and (2) the 1988 National Maternal and Infant Health Survey, a nationally representative sample of women who had live births in 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
2
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 29 publications
(26 reference statements)
5
94
2
3
Order By: Relevance
“…Additionally, the twelve-month prevalence rates of anxiety disorders were significantly greater for those patients deemed high utilizers of health care (29.3%) versus normal utilizers (11.9%; Schmitz & Kruse, 2002). Physically healthy adults experiencing depressive symptoms have been shown to utilize primary care services significantly more than nondepressed adults (Koopmans & Lamers, 2001;Mandl, Tronick, Brennan, Alpert, & Homer, 1999). In one study, patients experiencing depressive symptoms contacted their physicians more often than any other group with the exception of patients with heart disease (Koopmans & Lamers, 2001).…”
Section: Psychopathology Negative Affect and Adult Health Care Usementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the twelve-month prevalence rates of anxiety disorders were significantly greater for those patients deemed high utilizers of health care (29.3%) versus normal utilizers (11.9%; Schmitz & Kruse, 2002). Physically healthy adults experiencing depressive symptoms have been shown to utilize primary care services significantly more than nondepressed adults (Koopmans & Lamers, 2001;Mandl, Tronick, Brennan, Alpert, & Homer, 1999). In one study, patients experiencing depressive symptoms contacted their physicians more often than any other group with the exception of patients with heart disease (Koopmans & Lamers, 2001).…”
Section: Psychopathology Negative Affect and Adult Health Care Usementioning
confidence: 99%
“…In looking beyond anxiety, several studies have documented significant positive relationships between parental depression and pediatric health care use in children ages three to eighteen (Kramer, Warner, Olfson, Ebanks, Chaput, Weissman, 1998;Mandl, et al, 1999;Olfson, Marcus, Druss, Pincus, & Weissman, 2003;Weissman, Merikangas, John, Wickramaratne, et al, 1986). Children ages two to sixteen years categorized as high users of care have been shown to be twice as likely as low users to have parents that reported significant depressive symptoms (i.e.…”
Section: Maternal Negative Affect and Pediatric Health Care Usementioning
confidence: 99%
See 1 more Smart Citation
“…25,42,[47][48][49][50] Stressful newborn events, such as health problems and infant irritability, have also been associated with greater risk for postpartum depression. 25,44,51 Two prospective cohorts 52 were analyzed to determine whether women who frequently brought their neonates for (problem-oriented) primary care or emergency department visits were at an elevated risk of having depressive symptoms. Findings revealed that neonatal health care use-patterns predicted maternal risk for postpartum depression; mothers were more likely to have high levels of depressive symptoms if their infants had even 1 emergency department visit.…”
Section: Mood and Anxiety Disorders During The Postpartum Period Deprmentioning
confidence: 99%
“…The poorer compliance observed for depressed mothers is complementary to findings of more problemoriented and/or emergency visits for infants of depressed mothers. 66 The association of an unwanted pregnancy with incomplete well child care points to the importance of maternal attitude toward the child as a factor influencing the quality of care that the infant receives.…”
Section: Discussionmentioning
confidence: 99%